Functional and Object-Oriented Views in Embedded Software Modeling - Fernandes, João M. (2004)
The main aim of this article is to discuss how the functional and the object-oriented views can be inter-played in order to model the various modeling perspectives of an embedded system. We discuss if the object-oriented modeling paradigm, most likely the predominant one to develop nowadays software, in the broader sense of the term, is also adequate for modeling embedded software and how it must be conjugated with the functional paradigm. More specifically, we present how Data Flow Diagrams (DFDs), the main diagram in the traditional structured methods, can be integrated in an object-oriented development strategy based on the Unified Modeling Language (UML).